2008
DOI: 10.1080/02770900701847084
|View full text |Cite
|
Sign up to set email alerts
|

Normal Variation of Bronchial Reactivity in Nonasthmatics is Associated with the Level of Mite-Specific IgE

Abstract: Even in subjects without allergic symptoms, IgE-mediated sensitization does not appear to be all or nothing phenomenon influencing the normal variability of underlying airway reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In support of this, Nogalo et al. (17) recently showed in mite sensitive non‐asthmatic subjects a positive relationship between specific IgE to mite and AHR. We did not measure AHR in our children and cannot therefore confirm these associations directly.…”
Section: Discussionmentioning
confidence: 67%
“…In support of this, Nogalo et al. (17) recently showed in mite sensitive non‐asthmatic subjects a positive relationship between specific IgE to mite and AHR. We did not measure AHR in our children and cannot therefore confirm these associations directly.…”
Section: Discussionmentioning
confidence: 67%
“…Such association has been reported to show the association with not only the sensitization itself but also allergen types and each specific allergen 13, 17, 19–22. In other studies, the association of sensitization to house dust mite, cat allergen, timothy grass allergen, cockroach allergen, ragweed, and other specific allergen with AHR has been shown 12, 23–26. Sensitization to specific allergens is very important to develop asthma but there may be a great difference depending on regions particularly.…”
Section: Introductionmentioning
confidence: 88%
“…A previous study by Burrows and colleagues[13] investigated the associates of AHR in children, looking at the sizes of skin test wheals when analysing atopy, and demonstrated that the sizes of the reactions to mite, cat, dog and Aspergillus fumigatus were independently correlated with airway hyperresponsiveness, particularly when summed. Another study by Nogalo et al[12] looked specifically at the associations between airway hyperresponsiveness and level of specific mite specific IgE amongst mite-sensitised non-asthmatic children, and found that these were independently associated.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the US has demonstrated that AHR increased significantly amongst adult asthmatics with increasing size of skin test wheals to inhalant allergens[11]. A significant association was also reported amongst non-asthmatic individuals with increasing level of mite specific IgE[12]. …”
Section: Introductionmentioning
confidence: 99%